Una segunda especie de Krugiodendron (Rhamnaceae) en el Neotrópico - González Ramírez, José (2016)
Krugiodendron acuminatum, the second species of a previously monospecific genus is described and illustrated, based on material from Costa Rica and Mexico. This new species is immediately distin- guished from K. ferreum (Vahl) Urb., by the difference in the apex of the leaf blade; the first (as is implicit in the epithet) has an acuminate apex, while that of second is consistently emarginate.